Transmembrane Protein pUL50 of Human Cytomegalovirus Inhibits ISGylation by Downregulating UBE1L - Lee, Myoung Kyu; Kim, Ye Ji; Kim, Young-Eui; Han, Tae-Hee; Milbradt, Jens; Marschall, Manfred; Ahn, Jin-Hyun (Journal of Virology, 2018)
Interferon-stimulated gene 15 (ISG15) encodes a ubiquitin-like protein that can be conjugated to proteins via an enzymatic cascade involving the E1, E2, and E3 enzymes. ISG15 expression and protein ISGylation modulate viral infection; however, the viral mechanisms regulating the function of ISG15 and ISGylation are not well understood. We recently showed that ISGylation suppresses the growth of human cytomegalovirus (HCMV) at multiple steps of the virus life cycle and that the virus-encoded pUL26 protein inhibits protein ISGylation. In this study, we demonstrate that the HCMV UL50-encoded transmembrane protein, a component of the nuclear egress complex, also inhibits ISGylation. pULSO interacted with UBE1L, an E1activating enzyme for ISGylation, and (to a lesser extent) with ISG15, as did pUL26. However, unlike pUL26, pUL50 caused proteasomal degradation of UBE1L. The UBE1L level induced in human fibroblast cells by interferon beta treatment or virus infection was reduced by pULSO expression. This activity of pULSO involved the transmembrane (TM) domain within its C-terminal region, although pUL50 could interact with UBE1L in a manner independent of the TM domain. Consistently, colocalization of pUL50 with UBE1L was observed in cells treated with a proteasome inhibitor. Furthermore, we found that RNF170, an endoplasmic reticulum (ER)-associated ubiquitin E3 ligase, interacted with pUL50 and promoted pUL50-mediated UBE1L degradation via ubiquitination. Our results demonstrate a novel role for the pULSO transmembrane protein of HCMV in the regulation of protein ISGylation. IMPORTANCE Proteins can be conjugated covalently by ubiquitin or ubiquitin-like proteins, such as SUMO and ISG15. ISG15 is highly induced in viral infection, and ISG15 conjugation, termed ISGylation, plays important regulatory roles in viral growth. Although ISGylation has been shown to negatively affect many viruses, including human cytomegalovirus (HCMV), viral countermeasures that might modulate ISGylation are not well understood. In the present study, we show that the transmembrane protein encoded by HCMV UL50 inhibits ISGylation by causing proteasomal degradation of UBE1L, an E1activating enzyme for ISGylation. This pUL50 activity requires membrane targeting. In support of this finding, RNF170, an ER-associated ubiquitin E3 ligase, interacts with pULSO and promotes ULSO-mediated UBE1L ubiquitination and degradation. Our results provide the first evidence, to our knowledge, that viruses can regulate ISGylation by directly targeting the ISGylation E1 enzyme.
EVALuna2:35268